The Association Between Obesity and Social Isolation as Well as Loneliness in the Adult Population: A Systematic Review - Hajek, André (Diabetes Metab Syndr Obes, 2021)
PURPOSE: Obesity is associated with adverse health outcomes and can result in feelings of loneliness or social isolation, for example due to stigmatization. These factors are in turn associated with morbidity and mortality. Thus far, a systematic review is lacking with regard to the association between obesity, social isolation and loneliness. Therefore, our aim was to fill this gap in knowledge. MATERIALS AND METHODS: Three established electronic databases (PubMed, PsycInfo, as well as CINAHL) were searched. Observational studies examining the link between obesity and loneliness or social isolation were included. Disease-specific samples were excluded. RESULTS: In sum, six studies have been included. While some studies point to an association between obesity and increased loneliness levels, it should be acknowledged that findings are mixed. Study quality was quite high. CONCLUSION: This systematic review showed that the literature is inconclusive and incomplete. Further research is required to shed further light on these associations. Moreover, studies from countries outside Europe, based on longitudinal data and using objective assessments of obesity, are urgently required. Gender differences should be further explored.